Impacto psicosocial del test genetico en pacientes diagnosticados con cancer de mama o colorectal y familiares de alto riesgo: la atencion psico oncologica en el Hospital Universitario Sant Joan de Reus. - Sirgo, Agustina; Rubio, Beatriz; Torres, Asunción; Salvat, Mónica; Brunet, Joan (Psicooncología, 2005)
The main objective of this study is to describe psycho-oncological intervention at the Genetic Counselling Unit in the University Hospital Sant Joan. We also present data on a study which aims were: (1) to study the approach and understanding of the information given at the Genetic Counselling Unit and (2) to report the effect that genetic counselling has on the psychosocial adjustment for patients and family members. A total sample of 51 subjects were assessed (1) cancer patients who are candidates to a genetic testing, (2) cancer patients who do not meet the criteria for a genetic testing, (3) family members of cancer patients who do not meet the criteria for a genetic testing, and (4) family members of cancer patients who meet the criteria for a genetic testing. A number of variables were assessed regarding socio-demographic variables and type of tumor. Pre-genetic counselling variables evaluated were: reasons for attending the genetic counselling unit,beliefs about the cause of cancer in the family,and about the risk of developing cancer. Postgenetic counselling variables were: understanding of being or not candidate to genetic testing,advantages and disadvantages of being candidate to genetic testing, beliefs about the apparition of cancer in the family, conclusions from the visit, anxiety and depression and psychiatric history. The sample assessed shows a better understanding of the cancer risk they have and the reasons of having so many cancer cases in the family after the counselling visit. They rate the visit as important, informative and satisfactory,and they appear more relieved and relaxed.